Lymphocyte Proliferation Kinetics in Inhabitant of Takandeang Village, Mamuju: A High Background Radiation Areas in Indonesia - Dwi Ramadhani; Siti Nurhayati; Tur Rahardjo; Mukh Syaifudin (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Mamuju area in West Sulawesi considered as the high natural background radiation area in Indonesia. Our previous study showed that the mean mitotic index (MI) and nuclear division index (NDI) in lymphocytes of Botteng Village, Mamuju inhabitants was lower compared to control samples. To validate our previous study results, here in this study the evaluation of cell proliferation markers which were MI and NDI in peripheral blood lymphocytes (PBL) of Takandeang Village inhabitants was conducted.METHODS: A total 60 people were enrolled in this study, consisted of 35 samples from Takandeang Sub-Village and 25 from normal background radiation area. MI was calculated manually and automatically using Metafer 3.11.2 imaging system. The NDI defined as proportion of mononucleated, binucleated, trinucleated and tetranucleated cells were conducted using cytokinesis block micronucleus (CBMN) assay.RESULTS: The results of this study showed that the mean manual MI in Takandeang Sub-Village inhabitants was lower compared to control group (4.96±2.25 vs. 5.93±2.14). In contrast, the mean automatic MI (20.37±10.49 vs. 18.87±7.49) and NDI (1.555±0.174 vs. 1.523±0.112) in Takandeang Sub-Village inhabitants was higher compared to the control group. Statistical analysis revealed that the difference of mean manual MI, automatic MI and NDI in Takandeang Sub-Village inhabitants was not significantly different compared to the control group(p>0.05).CONCLUSION: It can be concluded that based on this study the chronic low radiation dose exposure in Takandeang Sub-Village, Mamuju has no significant effect on the lymphocytes proliferation.KEYWORDS: lymphocytes, mitotic index, nuclear division index, high background radiation